The Association Between Nutritional and Managemental Practices and the Incidence of Reproductive Disorders in Large Ruminant - Bilal, Muhammad; Faizan, Muhammad Adeel; Shahbaz, Muhammad; Adrian Shah, Shahzada Khurram; Saqib, Muhammad Najmus; Said, Arsalan; Muhammad, Sher; Noor, Maaz; Iqbal, Maryam; Ahmed, Umair (Indus Journal of Bioscience Research, 2025)
Reproductive health in large ruminants such as cattle and buffalo significantly impacts livestock productivity and farm profitability. Reproductive disorders, often due to poor management and nutrition, result in reduced fertility and poor herd performance. This study explores the combined effects of dietary and managerial practices on reproductive outcomes in major ruminants. It aims to offer evidence-based recommendations to improve reproductive efficiency and bridge gaps between theoretical knowledge and practical applications in livestock farming.This study examines the correlation between these practices and the prevalence of reproductive problems in large ruminants. A cross-sectional study was performed on 30 farms at University of Veterinary and Animal Sciences, Lahore, Pakistan, gathering data on animal nutrition, breeding methodologies, and the prevalence of reproductive problems, including infertility, extended calving intervals, and anovulation. Statistical analysis, encompassing Pearson’s correlation and multiple regression, was conducted to ascertain the principal determinants affecting reproductive health. The findings indicated that superior Body Condition Scores (BCS) were substantially correlated with reduced reproductive problems, while farms employing artificial insemination (AI) had a decreased rate of infertility compared to those utilizing natural mating. Multiple regression analysis established that body condition score (BCS) and breeding techniques were important predictors of reproductive health. These findings indicate that effective dietary control and modern breeding techniques, such as artificial insemination, can enhance fertility outcomes in ruminant agriculture. The research offers significant insights for optimizing herd management and reproductive efficacy, with possible implications for agricultural management and policy suggestions to augment animal productivity. The findings underscore the necessity for additional investigation into the particular nutritional elements influencing reproductive health and the enduring effects of breeding methodologies.